Access to Formal Childcare for Toddlers and Parental Employment and Earnings - Taiyo Fukai; Ayako Kondo (Institute of Labor Economics (IZA), 2024)
This study examines the effect of availability of accredited childcare centers, the most popular category of publicly licensed childcare centers in Japan, on mothers' employment and earnings. We focus on mothers with children less than two years old, most of whom are returning from parental leave to full-time work under excess demand for center-based childcare. We construct an instrument from the first-round assignment process of April enrollment and find that the enrollment to an accredited childcare center increases the employment rate of mothers of zero- and one-year-old children by 40.3 and 18.8 percentage points, respectively. The effect of such enrollment on mothers' annual salary is mostly explained by the extensive margin.
Keywords: J13; J22; H40; 330; childcare demand; childcare cost; maternal labor supply